ANALISIS LAPORAN KEUANGAN DALAM BENTUK RASIO TERHADAP KINERJA KEUANGAN PT. PUDJIADI AND SONS, TBK. DI BURSA EFEK INDONESIA - Cherly Dwi Qarlina (JURNAL MANAJEMEN, 2020)
This study analyzes financial statements on the financial performance of PT. Pudjiadi and Sons Tbk, which was reviewed based on liquidity ratios, leverage ratios, profitability ratios and company activity ratios. The purpose of this study was to determine the financial performance of PT. Pudjiadi and Sons Tbk. by analyzing financial statements using financial ratios. Based on the results of the study showed the financial performance of PT. Pudjiadi And Sons Tbk. based on liquidity ratios in the good category because they are able to pay short-term obligations when liquidated and are above 100%. Based on the leverage ratio of PT. Pudjiadi And Sons Tbk. is in the good category because not all of the company's funding is financed by debt, and is above the industry average. Based on the profitability ratio of PT. Pudjiadi and Sons Tbk. is in the good category because each sale generates company profits and is above the industry average. Based on the activity ratio of PT. Pudjiadi and Sons Tbk. in the good category because the company is able to maximize the capacity of assets owned and is above the industry average.